1996
DOI: 10.1002/(sici)1098-2795(199612)45:4<521::aid-mrd15>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of developmental competence, nuclear and ooplasmic maturation of calf oocytes

Abstract: In this study we evaluated nuclear and ooplasmic maturation of prepuberal calf oocytes to determine a possible cause for their low developmental competency. Calf oocytes resumed meiosis and arrested at the MII stage at rates similar to that of adult animals; however, zygotes derived from calf oocytes cleaved and developed at significantly lower rates. Ooplasmic maturation was assessed during oocyte maturation and fertilization. Transmission electron microscopy revealed that a majority of calf oocytes exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
13

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 73 publications
4
60
0
13
Order By: Relevance
“…Differences between prepubertal and adult oocytes have been characterized by different patterns in neosynthetic proteins (Khatir et al, 1998) and energy metabolism (Gandolfi et al, 1998), cytoplasmic organelle migration (Damiani et al, 1996) and reduced activity of some enzymes (Driancourt et al, 2001). Thus, a lower capacity to complete meiosis in oocytes derived from prepubertal whales may be supported by these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between prepubertal and adult oocytes have been characterized by different patterns in neosynthetic proteins (Khatir et al, 1998) and energy metabolism (Gandolfi et al, 1998), cytoplasmic organelle migration (Damiani et al, 1996) and reduced activity of some enzymes (Driancourt et al, 2001). Thus, a lower capacity to complete meiosis in oocytes derived from prepubertal whales may be supported by these findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by ultrastructural and spatial rearrangements of the ooplasm as well as by chemical changes of the molecules stored therein [58,59]. For this reason, in our recent studies, a set of experiments was designed to examine the effects of the exposure of bovine oocytes to a dose of Aroclor-1254 known to be detrimental to nuclear maturation and subsequent embryo development, on two important aspects of the cytoplasmic maturation of bovine oocytes: modulation of maternal mRNA polyadenylation [60] and cortical granules (CGs) migration and exocytosis [61].…”
Section: Pcbs and Cytoplasmic Maturationmentioning
confidence: 99%
“…It has been shown that follicular waves already start shortly after the birth of calves [14,15], and follicles of different size harbouring fertilizable oocytes are regularly observed [16,17,18]. Calf o o c y t e s h a v e b e e n s h o w n t o b e l e s s developmentally competent than their adult counterparts [19], and this limits the successful use of juvenile calves for commercial in vitro embryo p r o d u c ti o n w i t h t h e g o al o f r e d u c i n g t h e generation interval and accelerating the rate of genetic gain [20].…”
mentioning
confidence: 99%